Automotive Front Seat Design Trade-Offs: An OTSM-TRIZ-Based Approach - Altun, Koray (Otomotiv Mühendisleri Derneği, 2025)
Automotive seat design involves multiple and often conflicting requirements, including comfort, durability, safety, ergonomics, and climate control, which must be addressed simultaneously within a constrained design space. Conventional optimization and trade-off–based methods typically resolve these conflicts through compromise, leading to locally optimal solutions that limit inventive improvement and long-term adaptability. To overcome these limitations, this study proposes an inventive negotiation approach that integrates OTSM-TRIZ (“????? ?????? ???????? ????????” – General Theory of Powerful Thinking) with a structured multi-issue negotiation process. Rather than balancing requirements through direct trade-offs, the proposed workflow systematically maps contradictions, classifies design, need, and intermediary parameters, and supports the negotiation of inventive design choices. The approach is demonstrated through an automotive front-seat design case study, in which three alternative inventive concepts (composite materials, air bladder systems, and shape-memory materials) are evaluated. Each concept is analyzed with respect to its functional benefits, implementation challenges, and compatibility with long-term technology evolution trends. The results indicate that composite-based solutions currently offer the most feasible balance between comfort, durability, and manufacturability, while air bladder and shape-memory systems represent promising but less mature future-oriented options. The analysis further shows that hybrid configurations combining these concepts can move seat design closer to the Ideal Final Result (IFR). The main contribution of this study lies in demonstrating how OTSM-TRIZ and multi-issue negotiation can be jointly employed to manage both first-order and second-order contradictions, while explicitly linking design decisions to Trends of Engineering System Evolution. This integration provides a systematic and forward-looking framework for inventive decision-making in automotive engineering.
Keywords: Automotive Engineering (Other); Otomotiv Mühendisliği (Diğer)